Humor, silence, and civil society in Nigeria - Obadare, Ebenezer (Rochester studies in African history and the diaspora, 2016)
In Humor, Silence, and Civil Society in Nigeria, Ebenezer Obadare offers an innovative perspective on the idea and reality of civil society. Mobilizing a wide range of concepts and insights from political science, African studies, sociology, cultural studies, media studies, anthropology, communications theory, and international development, Obadare develops a notion of civil society that radically departs from the literature's axiomatic focus on voluntary civic associations and focuses instead on more informal strategies of resistance, such as humor and silence. Compellingly argued, Humor, Silence, and Civil Society in Nigeria raises provocative questions on a topic of keen importance for students, scholars, and policymakers. Ebenezer Obadare is associate professorof sociology at the University of Kansas. He is coeditor of Civic Agency in Africa: Arts of Resistance in the 21st Century (James Currey, 2014)